Les STO : histoire des Français requis en Allemagne nazie, 1942 - 1945 - Arnaud, Patrice 1972- (Histoire Seconde Guerre mondiale, 2010)
The history and social conditions of the French laborers in the Service du travail obligatoire in Nazi Germany during World War II